Mechanical Behaviour of Al2024-T3 Sheet Metal at Different Strain-rates and Temperatures. (2017) - Sancho, Rafael; Cendón, David; Gálvez, Francisco
Abstract: Aluminium alloys are widely used in the design of structural parts in the automotive and aircraft manufacturing because of their good specific mechanical properties. Many of the critical situations in these types of industries such as crash or impact phenomena as well as forming processes are related to high strain-rate deformations and adiabatic heating. Therefore, knowing flow and failure behaviour of materials under dynamic loading and applying reliable constitutive models is essential for designing the structural components safely. Johnson-Cook model is one of the most long-established constitutive relations in the dynamic field due to its simplicity and easy calibration. Nevertheless, empirical models do not collect and give information about the reason why materials behave in the way that they do, so micromechanical motivated continuum models are interesting for that. In the present work, authors analyse the mechanical dynamic behaviour of the aeronautical alloy Al2024-T3. An experimental study has been planned performing tests on sheet specimens at different strain-rates and temperatures to analyse the effect of these parameters. Low strain-rate experiments were conducted using a servo-hydraulic machine while high strain-rate tests were carried out using a split-Hopkinson tension bar. Testing temperatures were set at room and 373K by using a furnace made of resistors. The material behaviour is modelled using a micromechanical-based constitutive and a phenomenological failure model. Plastic flow of the material is defined by means of Orowan relation, where both temperature and strain-rate effect are included in the flow rule and the strain hardening law is just a function of equivalent plastic strain; while failure criterion is based on Cockcroft-Latham model. Strain fields on sample surfaces, which were used for obtaining the true stress-strain curves and performing a hybrid experimental-numerical failure calibration, were obtained by means of Digital Image Correlation technique.